Pengenalan Model PBL dengan Pendekatan Multimodal untuk Meningkatkan Kemampuan Berpikir Kritis dan Literasi Digital Siswa SMPN 1 Gerung - Qothrunnada, Qothrunnada; Zainuri, Baiq Nabila Saufika; Gunawan, Gunawan; Kosim, Kosim (Indonesian Journal of Education and Community Services, 2025)
This activity was carried out to introduce and implement the Problem-Based Learning (PBL) model with a multimodal approach to improve critical thinking skills and digital literacy of students at SMPN 1 Gerung. The background of the activity departed from the school's need to strengthen 21st-century skills through more interactive, challenging learning, and utilizing a variety of learning resources. The focus of the activity was directed at how the integration of various presentation modes, such as text, images, audio, and video, can support the problem-solving process systematically. The series of activities included an introduction to the concept of multimodal PBL, training in the use of multimodal media and learning resources, and mentoring implementation in the classroom. Teacher and student responses showed that this approach makes students more active, more analytical, and wiser in using digital media during the learning process. Overall, this activity recommends multimodal PBL as an alternative to strengthen science learning and a relevant strategy to encourage critical thinking skills and digital literacy at the junior high school level.